Social networks and suicidal behavior in adolescents: a case study - Villarreal Aguilar, Beltran (2024)
Suicide is the second cause of death in adolescents, with depression being the most frequently associated disorder, whose symptoms can be explained by Beck's cognitive triad. The case of a 15-year-old female adolescent is presented, a user of social networks as a platform for the information and manifestation of symptoms of depression, and of the desire to seek help; she was finally treated in an emergency room and hospitalized for the management of a depressive episode with suicidal attempt. This case allows to describe the process through which a social network directly influences a patient's mood disorder and its consequences.